2017
DOI: 10.3390/app7050458
|View full text |Cite
|
Sign up to set email alerts
|

Perfect Light Absorbers Made of Tungsten-Ceramic Membranes

Abstract: Plasmonic materials are expanding their concept; in addition to noble metals that are good conductors even at optical frequencies and support surface plasmon polaritons at the interface, other metals and refractory materials are now being used as plasmonic materials. In terms of complex permittivity at optical frequencies, these new plasmonic materials are, though not ideal, quite good to support surface plasmons. Numerical investigations of the optical properties have been revealing new capabilities of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Originally, metasurfaces have diverse potential and have exhibited various applications, stemming from their designs with large degree of freedom [ 14 , 15 , 16 ]. Most of metasurfaces intended to manipulate light waves for particular purposes such as focusing [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], polarization/phase control [ 24 , 25 , 26 , 27 , 28 , 29 ], perfect light absorption [ 30 , 31 , 32 , 33 , 34 , 35 ], and so on. The application of metasurfaces for FL enhancement has been tried in numerous studies; only a very small portion of the studies exceptionally reported prominent success in the very large FL-intensity enhancement more than 1000-fold to reference non-enhancing substrates [ 10 , 11 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Originally, metasurfaces have diverse potential and have exhibited various applications, stemming from their designs with large degree of freedom [ 14 , 15 , 16 ]. Most of metasurfaces intended to manipulate light waves for particular purposes such as focusing [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], polarization/phase control [ 24 , 25 , 26 , 27 , 28 , 29 ], perfect light absorption [ 30 , 31 , 32 , 33 , 34 , 35 ], and so on. The application of metasurfaces for FL enhancement has been tried in numerous studies; only a very small portion of the studies exceptionally reported prominent success in the very large FL-intensity enhancement more than 1000-fold to reference non-enhancing substrates [ 10 , 11 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Designs for metasurfaces have been mostly human knowledge based and optimizations from building blocks known previously. For example, metalenses [ 1 , 2 , 3 , 4 , 5 , 6 ], holograms [ 7 , 8 , 9 ], light absorbers [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], metagratings [ 17 , 18 , 19 ], luminescence-enhancing metasurfaces [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and so on, were fabricated in such ways. The designs for metasurfaces with a particular function are generally elaborate and limited to the domain conceivable from human knowledge, though they are sometimes assisted by optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Broadband PLAs are also established with a topology of metal-dielectric-metal layers. Broadband Structures previously demonstrated had different variations of simpler structures such as nanopillars made up of different variations of cylinders 20 , disks (cylinders) 21 , 22 , arrangement of crosses and cylinders 23 , nanopyramids (cones) 24 26 , rods (in shape of square) 27 , spheres, tetrahedral structure 28 , and even random deposition of particles 29 . A simple structure of square and in the end cross is used as a design in this research.…”
Section: Introductionmentioning
confidence: 99%
“…Previous structures involving tungsten were made up in the shape of cones 25 , 26 , but the designs presented in this paper are 2D, as they are not varying in z-direction (height). The design presented in 22 is also 2D but it is not designed for visible regime and it gives less absorbance. Since tungsten does not support surface plasmons in optical range, high absorbance is ascribed to impedance matching of tungsten absorber with the free space.…”
Section: Introductionmentioning
confidence: 99%